1988
DOI: 10.1677/joe.0.1190509
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor (IGF)-II and insulin, but not IGF-I, are mitogenic for fetal rat adrenal cells in vitro

Abstract: The agents controlling growth of the fetal adrenal gland are poorly defined. The purpose of the present study was to determine the factors required to promote proliferation of adrenal cells obtained from fetal rats at 20 days of gestation and grown in monolayer cell culture under serum-free conditions. Insulin stimulated [3H] thymidine incorporation into DNA at all concentrations (0.01-10 mg/l) tested. Rat insulin-like growth factor (IGF)-II in the presence of insulin promoted a dose-dependent increase in mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…One of the candidates for local adrenocortical autocrine or paracrine factors is insulin-like growth factors (IGFs). They have been reported to be mitogens for adreno¬ cortical cells in vitro (Horiba et al 1987;Van Dijk et al 1988;Naaman et al 1989). ACTH has been found to increase IGF-II mRNA expression in human fetal adrenocortical cells (Voutilainen & Miller, 1987), and IGF-I peptide synthesis in bovine adrenocortical cells (Penhoat et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…One of the candidates for local adrenocortical autocrine or paracrine factors is insulin-like growth factors (IGFs). They have been reported to be mitogens for adreno¬ cortical cells in vitro (Horiba et al 1987;Van Dijk et al 1988;Naaman et al 1989). ACTH has been found to increase IGF-II mRNA expression in human fetal adrenocortical cells (Voutilainen & Miller, 1987), and IGF-I peptide synthesis in bovine adrenocortical cells (Penhoat et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…ACTH may act directly as a trophic factor, indirectly via the adrenal glucocorticoids or by stimulation of a local or paracrine growth factor such as fibroblast growth factor (FGF) or the in sulin-like growth factors (IG Fs). IGF I and IGF II mRNA's have been localized in the adrenal cortex of the human fetus [27] and in the presence of insulin, IGF II has been shown to stimulate mitogenesis of fetal rat adrenocortical cells [28,29]. ACTH enhances the expression of FGF in the human fetal adrenal and in vitro studies have shown that FGF stimulates the growth of adrenocortical cells [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-II is a potent mitogen in cultured fetal rat adrenocortical cells (Van Dijk et al, 1988), whereas IGF-I is an important regulator of postnatal adrenocortical growth. IGF-I may also play a role in the induction and maintenance of steroidogenic function of adrenocortical cells, since both IGF-I peptide and its receptors have been detected in the adrenal cortex of various species (Feige and Baird, 1991;Penhoat et al, 1988;Pillion et al, 1988Pillion et al, , 1989.…”
Section: Igf-i In the Adrenal Cortexmentioning
confidence: 99%